2007
DOI: 10.1136/adc.2005.092379
|View full text |Cite
|
Sign up to set email alerts
|

Plasma levels of active ghrelin until 8 weeks after birth in preterm infants: relationship with anthropometric and biochemical measures

Abstract: This study investigated the relationship between plasma levels of ghrelin and postnatal growth in preterm infants. The levels of active ghrelin in cord blood and in plasma in 25 very low birthweight (VLBW) infants were measured. The results indicate that the levels of circulating active ghrelin markedly increases after birth in VLBW infants, and suggest that the increased levels of ghrelin reflects the maturation of ghrelin production in the stomach and an increased physiological need for ghrelin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 5 publications
2
17
0
Order By: Relevance
“…However, high ghrelin levels may also be explained by an intrinsic characteristic of the preterm born infants. In fact, in the study by Shimizu et al (8), it was shown that active ghrelin levels were increased in low birth weight infants in the first 8 weeks of life, and similar to our study the ghrelin levels did not differ between the AGA and SGA infants. The inverse relation of ghrelin with gestational age in our study may also imply this hypothesis.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…However, high ghrelin levels may also be explained by an intrinsic characteristic of the preterm born infants. In fact, in the study by Shimizu et al (8), it was shown that active ghrelin levels were increased in low birth weight infants in the first 8 weeks of life, and similar to our study the ghrelin levels did not differ between the AGA and SGA infants. The inverse relation of ghrelin with gestational age in our study may also imply this hypothesis.…”
Section: Discussionsupporting
confidence: 76%
“…This finding shows that the increased levels of ghrelin in preterm born children in the early neonatal period (7,8) are sustained up to prepubertal ages. This increase in ghrelin levels may be needed for the growth of these children, but it does not seem to be related to the degree of CUG because preterm SGA infants had significantly higher CUG than preterm AGA children in spite of similar ghrelin levels.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Accordingly, James et al (31) postulated that lower cord ghrelin levels were associated with gradual weight gain from birth to 3 months of age. It has been shown that ghrelin levels increase in preterm infants early in the neonatal period (13,23,29) and this increase is not inhibited by food intake (13,29). So, ghrelin may play a physiological role in fetal adaptation to intrauterine malnutrition, and early changes in active ghrelin levels in the early neonatal period in preterm infants might suggest a possible role of active ghrelin in the adaptation of the neonatal metabolism to the extrauterine life with an anabolic drive during this growth and development period.…”
Section: Discussionmentioning
confidence: 99%